Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12883-016-0637-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and follow-up of posterior inferior cerebellar artery dissection complicated with ischemic stroke assisted by T1-VISTA: a report of two cases

Abstract: BackgroundVolume isotropic turbo spin-echo acquisition (VISTA) is a new method similar to the 3D black-blood imaging method that enables visualization of a intramural hematoma. T1-VISTA has recently been applied in the diagnosis of intracranial arterial dissection. However, the identification of an intramural hematoma in posterior inferior cerebellar dissection (PICA-D) by T1-VISTA has only rarely been reported.Case presentationWe herein report two patients who suffered from PICA-D complicated with ischemic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Recent advances in MRI may improve the diagnostic accuracy to detect the presence and extent of PICA dissection. [13] This study may also be valuable given that follow-up imaging studies were performed in as many as 86% of patients with AD-related CI [Table 3]. Progression of AD in the acute phase (i.e., the progression within 14 days of onset) was observed in 2 of the 14 patients (14%), which was compatible with current literature.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Recent advances in MRI may improve the diagnostic accuracy to detect the presence and extent of PICA dissection. [13] This study may also be valuable given that follow-up imaging studies were performed in as many as 86% of patients with AD-related CI [Table 3]. Progression of AD in the acute phase (i.e., the progression within 14 days of onset) was observed in 2 of the 14 patients (14%), which was compatible with current literature.…”
Section: Discussionsupporting
confidence: 83%
“…Recent advances in MRI may improve the diagnostic accuracy to detect the presence and extent of PICA dissection. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Although isolated PICA dissection is rare, it had been underdiagnosed which leads to the occurrence of ischemic stroke of the posterior circulation [5]. Recent studies have shown that isolated PICA dissection can be diagnosed using HR vw-MRI [13]. In most case studies, intramural hematoma, dilated lumen, or pearl-and-string appearance were seen on HR vw-MRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still difficult to accurately diagnose PICA dissection because the size of the PICA is very small. Recent studies have diagnosed isolated PICA dissection in patients by using high-resolution vessel wall MRI (HR vw-MRI), in which a T1 hyperintense intramural hematoma was the main finding [13]. Although an intramural hematoma is a pathognomonic sign of PICA dissection, it may be necessary to distinguish it from intraplaque hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Survey of studies focused on 1 vasculopathy revealed intracranial atherosclerotic disease (ICAD) to be the most commonly studied vasculopathy (49%, n = 62, references in the On-line Appendix), followed by arterial dissection (13%, n = 16), 10,12 -26 aneurysm (8%, n = 10), [27][28][29][30][31][32][33][34][35][36] vasculitis (5%, n = 6), [37][38][39][40][41][42] Moyamoya disease (3%, n = 4), [43][44][45][46] postendovascular changes (2%, n = 3), [47][48][49] and reversible cerebral vasoconstriction syndrome (1%, n = 1) 50 ( Fig 3C). Among the 16 publications investigating arterial dissections, 11 used VWI 12,[14][15][16][17][18][22][23][24][25][26] and the other 5 publications 10,13,[19][20][21] assessed intramural hematoma signal characteristics on conventional MR imaging. Note that 21% of the studies examined $2 types of vasculopathies; a breakdown of the types of vasculopathies studied among these publications is further illustrated in the piein-pie chart.…”
Section: Publication Trendsmentioning
confidence: 99%